Global polarization of Ξ and Ω hyperons in Au + Au collisions at √sNN = 200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert; Weidenkaff, Philipp (Physical review letters, 2021)
Global polarization of Ξ and Ω hyperons has been measured for the first time in Au+Au collisions at √sNN=200 GeV. The measurements of the Ξ− and ¯Ξ+ hyperon polarization have been performed by two independent methods, via analysis of the angular distribution of the daughter particles in the parity violating weak decay Ξ→Λ+π, as well as by measuring the polarization of the daughter Λ hyperon, polarized via polarization transfer from its parent. The polarization, obtained by combining the results from the two methods and averaged over Ξ− and ¯Ξ+, is measured to be ⟨PΞ⟩=0.47±0.10(stat)±0.23(syst)% for the collision centrality 20%-80%. The ⟨PΞ⟩ is found to be slightly larger than the inclusive Λ polarization and in reasonable agreement with a multiphase transport model. The ⟨PΞ⟩ is found to follow the centrality dependence of the vorticity predicted in the model, increasing toward more peripheral collisions. The global polarization of Ω, ⟨PΩ⟩=1.11±0.87(stat)±1.97(syst)% was obtained by measuring the polarization of daughter Λ in the decay Ω→Λ+K, assuming the polarization transfer factor CΩΛ=1.
Gesehen am 02.09.2021
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt